2020
DOI: 10.1177/1129729820937486
|View full text |Cite
|
Sign up to set email alerts
|

Preliminary balloon dilation of both saphenous fascia and the saphenous vein increases the below-knee fistula patency, but not maturation

Abstract: Objective: There is no reliable secondary site for fistula creation in patients with preclusions for further use of upper extremity vessels as viable hemodialysis access. Below-knee vessels resemble the forearm vascular anatomy and, therefore, methods to improve the outcomes of fistula creation at this level would also help to improve the quality of life for those patients. The aim of the present study was to examine the efforts to improve the functionality of below-k… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 18 publications
0
2
0
Order By: Relevance
“…In addition, the wall structure of the saphenous vein and compression of the surrounding fascia may cause insufficient dilatation and maturation as well as increased neointimal hyperplasia. Kahraman et al reported that they could initiate hemodialysis in only three (27.3%) of eleven tibial saphenous fistula cases in which they applied balloon dilation to the saphenous vein and its fascia while creating the ankle fistula [ 2 ]. Also, lower extremity edema, which may be caused due to volume burden or impaired venous circulation due to fistula, may lead to difficult cannulation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, the wall structure of the saphenous vein and compression of the surrounding fascia may cause insufficient dilatation and maturation as well as increased neointimal hyperplasia. Kahraman et al reported that they could initiate hemodialysis in only three (27.3%) of eleven tibial saphenous fistula cases in which they applied balloon dilation to the saphenous vein and its fascia while creating the ankle fistula [ 2 ]. Also, lower extremity edema, which may be caused due to volume burden or impaired venous circulation due to fistula, may lead to difficult cannulation.…”
Section: Discussionmentioning
confidence: 99%
“…Creating an autogenous arteriovenous fistula for the lower extremities is extremely rare, and usually, a saphenofemoral AV fistula is used [ 1 ]. Interventions below the knee are rare due to maturation problems related to inadequate dilatation of the great saphenous vein, frequent stenosis due to intimal hyperplasia, and ischemic complications due to diabetes and peripheral arterial disease [ 2 , 3 ]. Typically, the posterior tibial artery is used in this body region.…”
Section: Introductionmentioning
confidence: 99%